“I'm Gen Z—Can I Buy a House?” The Moderating Role of Sharia Risk Tolerance and Islamic Financial Planning in Homeownership Intention Models - Ni'ma Umar; Ahmad Syarief Iskandar; Ishak Ishak (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to investigate the impact of the reality of the gig economy, especially income volatility and the intensity of freelance work on the interest in home ownership among Generation Z and analyze the role of Islamic financial literacy and Islamic risk tolerance as protective mechanisms (moderation) amid economic uncertainty. Design/methodology/approach – Using a quantitative explanatory approach, primary data were collected through questionnaires from 160 Generation Z respondents who work as freelancers (gig workers) and are homeless, drawn through purposive sampling. The data were then analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 4.0 software.. Finding/Results – The test results demonstrate that access to Islamic financing, gig work intensity, housing affordability, Islamic financial literacy, Islamic consumption orientation, and perceived job security have a positive and significant influence on homeownership interest. Conversely, income volatility has a very significant negative impact on this interest. In terms of direct influence, Islamic financial planning and Islamic risk tolerance do not have a significant effect. Originality/Value – This research fills a gap in the literature regarding barriers to home ownership for Gen Z gig workers, which has often been overlooked in mainstream economic studies. Its primary contribution lies in empirically testing Sharia Risk Tolerance as a crucial moderating mechanism that effectively neutralizes the negative impact of income volatility on long-term housing decisions.